Translation of Moroccan Paremias Into French: Equivalence Between Paremias Starting With « lli » in Moroccan Arabic and « qui » in French - Hamdane, Hanane (Taikomoji kalbotyra, 2021)
The purpose of this study is to search for equivalences between the paremias in Moroccan Arabic and French. Our study is based on a corpus of Moroccan and French paremias belonging to the same class: Moroccan paremias starting with “lli” and French paremias starting with “qui” (which is the French equivalent of “lli”).The corpus was drawn mainly from works identifying phraseological units, audio recordings of spontaneous conversations of speakers of Moroccan Arabic and notes taken while listening to conversations in different contexts. After the morpho-phonological transcription of the corpus, we proceeded to the analysis of the phraseologies in order to: (i) highlight the convergences and divergences between paremiological phraseology in Moroccan Arabic and French, and their degrees of equivalence, and (ii) check the existence of paremiological universals by studying the equivalences between two different languages.
Keywords: paremias; paremiological equivalence; proverbs; Moroccan Arabic; translation